Beginning Mac OS X Snow Leopard Server - Edge, Charles S. (Apress, 2012)
Dave Coyle earned his PhD in thermochronology in 1992. Research in thermal modeling and crustal evolution at the Max-Planck Institute for Nuclear Physics (Heidelberg Germany) lead to a career in software development. David has been concentrating on Apple technologies since 1997 and is a certified Apple System Administrator. Joe Kissell is Senior Editor of TidBITS, a Web site and weekly email newsletter about the Macintosh and the Internet, and the author of numerous print and electronic books about Macintosh software, including the best-selling Take Control of Mac OS X Backups. He is also a Senior Contributor to Macworld. Joe has worked in the Mac software industry since the early 1990s, and previously managed software development for Nisus Software and Kensington Technology Group. He currently lives in Paris, France.